Modelling the dynamics of regional employment–population ratios and their commonality. (February 2016) - Dixon, Robert; Lim, Guay
This paper looks at movements over time in regional employment–population ratios, an important and much neglected determinant of regional performance. We utilise data on gross flows into and out of employment and focus on information contained in the transition rates. The paper applies an unobserved components econometric model to a panel of Australian data to identify and explain the evolution of regional employment–population ratios over time. The approach identifies a common (i.e. nationwide) factor while allowing for region-specific effects, including region-specific impacts of the common factor. The contribution of the common factor to changes in regional employment–population ratios ranges between 38% and 80%. Conversely, regional elements explain between 20% and 62% of changes. The findings highlight the importance of adopting explicit regional employment policies as a complement to national policy.